(In)stability of ligands at the surface of inorganic nanoparticles: A forgotten question in nanomedicine?. (August 2022) - Le Goas, Marine; Saber, Justine; Bolívar, Sara González; Rabanel, Jean-Michel; Awogni, Jean-Marc; Boffito, Daria C.; Banquy, Xavier
Abstract: Multiple inorganic nanoparticles (NPs) are currently being developed for nanomedicine. Various core materials and shapes are explored, but they all display a common hybrid structure, with organic ligands on their surface. These ligands play a key role in the NP colloidal stability and surface properties, and therefore strongly impact the biological fate of the NPs. However, ligands may be subject to reorganization, degradation, desorption, and exchange, both during their shelf-life and upon exposure to a biological environment. The question of ligand (in)stability at the surface of inorganic NPs has been little addressed in the literature. The goal of this review is to provide a portrait of this critical phenomenon. We identify and review here the different mechanisms likely to promote ligand instability and discuss the resulting biological fate of ligands. This review is aimed to provide a better understanding of these phenomena and to help researchers to design NP-based medicines with better clinical efficacy and translation ability. Graphical Abstract: ga1 Highlights: The stability of surface ligands on inorganic nanoparticles has been little addressed. Multiple mechanisms are shown to alter the surface ligands of inorganic NPs. Ligand degradation can occur during storage and upon exposure to biological environments. Ligand instability may strongly impact the properties and efficacy of nanoparticles. There is a critical need to develop analytical tools to study this phenomenon.